OPTIMALISASI SIFAT MEKANIK SERAT ALAM DARI SERBUK KAYU ULIN MELALUI TEKNIK PENGERINGAN SEBAGAI PENGUAT MATERIAL BIOKOMPOSIT ANJUNGAN KAPAL - Purwanto Purwanto; Erwin Sutantyo; Heri Kiswanto; Khoirotun Nafillah; Rifki Arya Wiguna; Arif Rakhman Suharso (Construction and Material Journal, 2023)
Ironwood (eusideroxylon zwageri) is a type of wood that has great potential for industrial development. Currently, forest exploitation activities and the wood industry produce 30%-60% solid wood waste and have not been utilized optimally. One way to use it is to make composite materials. The purpose of this study was to determine the most optimal drying technique of ironwood powder, to provide information on the morphology, content and functional groups as well as the mechanical strength of the biocomposite with a volume fraction ratio. The ironwood powder samples in this study were characterized using the SEM-EDX, FTIR, and Vickers hardness tests. The results of the SEM test obtained information that the morphology of all samples had similarities, namely the surface was rough and the measured diameter of the sample ranged from 50-100 Âµm. While the EDX test obtained information that all samples had high carbon and oxygen content. The FTIR test results showed that ironwood powder had a cellulose content as evidenced by the absorption peaks and chemical bonds that were the same as pure cellulose. The results of the mechanical test on the biocomposite showed that sample C had the highest average HV value of 13.3 N/m2, while sample E had an average HV value of 12.26 N/m2 below the HV value of sample E. Meanwhile, sample A obtained the lowest hardness value with an average HV 5.93 N/m2.